Agreement between nosologist and cardiovascular health study review of deaths: implications of coding differences. - Ives, Diane G; Samuel, Paulraj; Psaty, Bruce M; Kuller, Lewis H (J Am Geriatr Soc, 2009)
OBJECTIVES: To compare nosologist coding of underlying cause of death according to the death certificate with adjudicated cause of death for subjects aged 65 and older in the Cardiovascular Health Study (CHS). DESIGN: Observational. SETTING: Four communities: Forsyth County, North Carolina (Wake Forest University); Sacramento County, California (University of California at Davis); Washington County, Maryland (Johns Hopkins University); and Pittsburgh, Pennsylvania (University of Pittsburgh). PARTICIPANTS: Men and women aged 65 and older participating in CHS, a longitudinal study of coronary heart disease and stroke, who died through June 2004. MEASUREMENTS: The CHS centrally adjudicated underlying cause of death for 3,194 fatal events from June 1989 to June 2004 using medical records, death certificates, proxy interviews, and autopsies, and results were compared with underlying cause of death assigned by a trained nosologist based on death certificate only. RESULTS: Comparison of 3,194 CHS versus nosologist underlying cause of death revealed moderate agreement except for cancer (kappa=0.91, 95% confidence interval (CI)=0.89-0.93). kappas varied according to category (coronary heart disease, kappa=0.61, 95% CI=0.58-0.64; stroke, kappa=0.59, 95% CI=0.54-0.64; chronic obstructive pulmonary disease, kappa=0.58, 95% CI=0.51-0.65; dementia, kappa=0.40, 95% CI=0.34-0.45; and pneumonia, kappa=0.35, 95% CI=0.29-0.42). Differences between CHS and nosologist coding of dementia were found especially in older ages in the sex and race categories. CHS attributed 340 (10.6%) deaths due to dementia, whereas nosologist coding attributed only 113 (3.5%) to dementia as the underlying cause. CONCLUSION: Studies that use only death certificates to determine cause of death may result in misclassification and potential bias. Changing trends in cause-specific mortality in older individuals may be a function of classification process rather than incidence and case fatality.
Keywords: Aged; Aged, 80 and over; Cause of Death; Coronary Disease; Death Certificates; Female; Forms and Records Control; Humans; Longitudinal Studies; Male; Stroke